Risk of myocardial infarction and stroke following bloodstream infection: a population-based self-controlled case series - Ashley Akbari; Haroon Ahmed; Jonathan Underwood; Victoria Best; Nicola Reeve (Open Heart)
Background Cardiovascular disease (CVD) events triggered by inflammation are an underappreciated and poorly quantified cause of morbidity and mortality in patients with bloodstream infections (BSIs). We aimed to determine the risk of myocardial infarction (MI) and stroke after BSI.Methods This self-controlled case series study was conducted within the Secure Anonymised Information Linkage Databank, containing anonymised population-scale electronic health record data for Wales, UK. We included adults with community-acquired BSI between 2010 and 2020. MI and stroke were determined from International Classification of Disease Version 10 coded admissions. Predefined risk periods after BSI were compared with the baseline period using pseudo-Poisson regression adjusted for age. Maximum C-reactive protein (CRP), a proxy for the magnitude of the inflammatory response, was determined within the first 7 days after BSI.Results We identified 50 450 individuals with MI and 56 890 with stroke, of whom 1000 and 1290, respectively, also had at least one community-associated BSI. The risk of MI was most elevated in the first 1–7 days after BSI (adjusted incidence rate ratio (IRR) (95% CI): 9.67 (6.54 to 14.3)) and returned to baseline after 28 days. The risk was similarly elevated for stroke.The largest magnitude of risk was observed for those with a maximal CRP>300 mg/L (MI IRR: 21.54 (9.57 to 48.52); stroke IRR: 6.94 (3.14 to 15.32)).Conclusion BSI is associated with an increased risk of CVD events in the first 2 weeks after infection. Greater systemic inflammation was associated with a higher risk of CVD events and suggests targeting the inflammatory response caused by BSI warrants further study.